The Process of Development of Industrial Enterprises in Kashadarya During Independence (On the Example of Shurtangaz) (Czech Journal of Multidisciplinary Innovations, 2022)
Shurtan Gas Chemical Complex is one of the largest gas companies in Uzbekistan. Uzbekneftegaz is a unitary subsidiary of the national holding company. It is located in Shurtan town of Guzar district of Kashkadarya region. It occupies an area of more than 150 hectares.